Parenting pathways to friendship: how Self-Control and emotion management skills mediate preschoolers’ social lives in China? - Dexian Li; Wencan Li; Xin Lin; Xingchen Zhu (BMC Psychology)
Abstract Background Parenting styles have been identified as significant factors influencing children’s social behaviors, particularly in their peer interactions. However, the specific mechanisms through which different parenting styles affect these behaviors, particularly among children aged 3–6, remain understudied. Objective Applying the theoretical frameworks of SLT and SRT, this study aimed to explore how authoritarian and authoritative parenting styles affect peer interactions in 3- and 6-year-old children, focusing on the mediating role of self-control and emotion management skills. Methodology A survey was conducted using a stratified cluster random sampling method, with 2,397 participants recruited from 16 kindergartens in 10 provinces and 7 regions across the country. The study employed descriptive statistics, Pearson correlation, structural equation modeling, and bootstrap method to examine the relationships between parenting styles, self-control, emotion management skills, and peer interactions. Results Authoritarian parenting style is negatively and strongly correlated with children’s peer interactions ( β = -0.57, p > 0.05); self-control fully mediated this relationship, accounting for 32.79%, and emotion management skills partially mediated 16.39%. Authoritative parenting had a direct effect on peer interactions ( β = 0.07, p < 0.05); self-control partially mediated 26.47% and emotion management skills 35.29% of the total effect; individual self-control (stable psychological traits) and emotion management skills (dynamic psychological processes) are important bridges through which family parenting practices influence the socialization process of children, and are also essential internal resources for achieving positive social adjustment. Conclusions This study contributes to the existing literature by providing empirical evidence on the differing effects of authoritarian and authoritative parenting styles on children’s peer interactions, while highlighting the crucial roles of self-control and emotion management skills in these relationships. The findings offer practical implications for parents and educators in Chinese families, suggesting effective parenting strategies that promote positive social development among young children.